Legal Responsibility of PPK As An Agency In The Procurement of Goods and Services - Engeli Yuliana Lumaing; Indrasatya Octavianus Nasirun; Yoan Barbara Runtunuwu; Novita Mongdong; Rusyandi Rusyandi; Romi Mesra (Labor Program Studi Pendidikan Sosiologi, 2023)
The person designated as the owner of the job by the Budget User or Power of Budget User and in charge of carrying out the acquisition of goods and services is known as the Commitment Maker Officer. Contract-based procurement operations necessitate a high level of comprehension and/or proficiency, beginning with the stages of purchase planning, purchase execution, control, contract signing, and reporting and submission of work results. As a result, the PPK acts as its representative when forming alliances or agreements with other parties; in the absence of the Office of the Commitment Maker, the instance is unable to do so. The Office of the Commitment Maker determines whether a procurement of goods and services within an agency is successful or unsuccessful. This indicates that the fundamental functions of the Office of Commitment Makers are intimately tied to the utilization of the State budget since their execution calls for a distinct set of skills, accountability, and rigor than those of another administrative officer. State losses from damage or other claim claims will arise from errors in the Office of the Commitment Maker's discharge of its obligations